ANALISIS RASIO KEUANGAN ORGANISASI PENGELOLA ZAKAT (BAZNAS) - Afina Azzahra; Darma Sari; Dea Angraeni; Ersi Sisdianto (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This study is targeted at analyzing and observing the financial performance of BAZNAS/National Amil Zakat Agency in Lampung from 2021-2023. This study uses efficiency, activity, development and amil fund ratios that are in line with the BAZNAS study. This study has quantitative data from BAZNAS Lampung financial data from 2021-2023. To collect data, we use documentation & observation using quantitative descriptive methods. Through the activity ratio analysis, it shows that the results are quite optimal, and BAZNAS is classified as good for storing and distributing Infaq, Zakat & Alms (ZIS) funds. The efficient ratio shows relatively optimal results even though the ratio of operating costs to mil rights and to the number of ammil rights is not optimal, but the ratio of storage, human resources and capital funds can be called optimal. Also the amil fund is classified as good. However, the development ratio shows results that are not optimal, whereas the development ratio of distribution and collection shows results that are not yet good.